The Possibility of Boron Carbide Coating Formation by Using a Coaxial Magnetoplasma Accelerator; Applied Mechanics and Materials; Vol. 1097 : Nanomaterials and Surface Technologies, Materials Applications - Sivkov A. A. Aleksandr Anatolyevich (Surface and Coating Materials Technologies and Engineering, 2015)
Title screen